An adapted Clavien-Dindo scoring system in trauma as a clinically meaningful nonmortality endpoint. Issue 2 (August 2017) - Naumann, David N.; Vincent, Laura E.; Pearson, Nicola; Beaven, Alastair; Smith, Iain M.; Smith, Kieran; Toman, Emma; Dorrance, Helen R.; Porter, Keith; Wade, Charles E.; Cotton, Bryan A.; Holcomb, John B.; et al.
Abstract : BACKGROUND: There is no consensus on reporting nonmortality trauma complications in a graded manner. The Clavien-Dindo scale of complications was originally for elective surgery and requires adaptation to provide meaningful data for trauma patients. In particular, the original score does not account for those treated without surgery. We report an adapted Clavien-Dindo in trauma (ACDiT) scale and apply it to patients managed operatively and nonoperatively. METHODS: A combined prospective and retrospective international multicenter observational study was undertaken to apply the ACDiT scale to 484 trauma patients at three university teaching hospitals (Birmingham, England (n = 303); Houston, Texas (n = 113); and Glasgow, Scotland (n = 68)). These included both intensive care unit (ICU) and non–ICU-managed patients. The Clavien-Dindo scoring system was adapted for trauma patients based on consensus amongst an international collaboration of trauma specialists at these sites. Data included whether initial patients were managed operatively or nonoperatively. Complication grades were compared with hospital-free and ICU-free days as other outcome measures of patient morbidity. RESULTS: Two hundred seventeen (44.8%) of 484 patients experienced complications, of whom 61 (28.1%) of 217 died (grade V). The remainder consisted of grades I (n = 20), II (n = 60), III (n = 24), and IV (n = 52). There was a strong association between higher ACDiT grade category and lower number of hospital-free and ICU-free days ( p < 0.01). Eighty-eight patients with complications did not require surgery, validating the score's usefulness in patients managed nonoperatively. CONCLUSION: The ACDiT scale can be used to grade the severity of posttrauma complications in patients managed both operatively and nonoperatively. It provides clinically meaningful data for morbidity and mortality meetings and other quality improvement exercises. LEVEL OF EVIDENCE: Prognostic, level IV. Abstract : Supplemental digital content is available in the text.